Association of OPG gene polymorphisms with the risk of knee osteoarthritis among Chinese people. Issue 6 (11th April 2019) - Qi, Yuxin; An, Feimeng; Wang, Jiaqi; Liu, Yuan; Gao, Hongyan; Ge, Zhe; Jiang, Enze; Cai, Donggao; Shi, Jianping; Wang, Jianzhong
Abstract: Background: Osteoarthritis (OA) is usually recognized to have a genetic factor, and in our study, we performed a case–control study to analyze the association between 14 single nucleotide polymorphisms (SNPs) in OPG and the risk of knee OA in a Chinese Han population. Methods: Fourteen OPG SNPs were assayed using MassARRAY in 393 patients clinically and radiographically diagnosed with knee OA and in 500 controls. Allelic and genotypic frequencies were compared between the groups. Logistic regression adjusting for age and gender was used to estimate risk associations between specific genotypes and knee OA by computing odds ratios (ORs) and 95% confidence intervals (95% CIs). Results: We found that the minor alleles of six SNPs in OPG were associated with an increased or decreased risk of knee OA in the allelic model analysis. In the genetic model analysis, we found that rs1905786, rs1032128, rs3134058, rs11573828, rs11573849, rs3134056, and rs1564861 were associated with an increased or decreased risk of knee OA before adjusted by sex and age. And after adjustment, three SNPs (rs1485286, rs1905786, and rs1032128) were identified to have a negative effect on knee OA. Conclusion: Our results verify that genetic variants of OPG contribute to knee OA susceptibility in the population of northern China. These genetic associations may identify individuals at a particularly high risk of developing knee OA. Abstract : Osteoarthritis (OA) is usually recognized to have a genetic factor, and in our study, we performed a case–control study to analyze the association between 14 single nucleotide polymorphisms (SNPs) in OPG and the risk of knee OA in a Chinese Han population. Our results verify that genetic variants of OPG contribute to knee OA susceptibility in the population of northern China. These genetic associations may identify individuals at a particularly high risk of developing knee OA.